Proline content and yield components of local corn cultivars from Kisar Island, Maluku, Indonesia (International Journal of Plant Biology, 2016)
Proline is one of amino acid that usually accumulates inside the plant cell when facing drought stress. The accumulation of proline can protect the plant cell from damage during drought. The aim of this research was to determine proline content and yield components of local corn cultivars from Kisar Island, Maluku, Indonesia. The field trial was organized using randomized block design with three replicates. Six local corn cultivars found in Kisar Island (Deep Yellow, Early Maturing Yellow, Red Blood, Rubby Brown Cob, Waxy, and White) were used as plant materials and a recommended tolerance variety (Srikandi) was taken as reference group. Proline content was determined using ninhydrin method. Yield components variables included cob weight (at harvest, after air dry, after oven dried, at 12% of water content), cob water content at harvest, cob length, cob diameter, number of seed row per cob, number of seed per cob, and cob yield at 12% of water content. Data collected was analysed with analysis of variance followed by Duncan multiple range test at the significant level 0.05 using Statistical Analysis System/SAS software version 9.0. The result shows that highest proline content and yield components (except for cob water content) was showed by the Deep Yellow cultivar. The lowest proline content was showed by Rubby Brown Cob cultivar. The lowest corn yield components was showed by Red Blood local cultivar. Deep Yellow cultivar can be proposed as superior drought tolerance variety, and can be recommended for further wide cultivation in Maluku province.